Impact of the unimodal molar mass distribution on the mechanical behavior of polymer nanocomposites below the glass transition temperature: A generic, coarse-grained molecular dynamics study - Ries, Maximilian; Laubert, Lukas; Steinmann, Paul; Pfaller, Sebastian (European Journal of Mechanics A-Solids, 2024)
Polymer nanocomposites (PNCs) have shown great potential to meet the ever-growing requirements of modern engineering applications. Nowadays, molecular dynamics (MD) simulations are increasingly employed to complement experimental work and thereby gain a deeper understanding of the complex structure–property relations of PNCs. However, with respect to the thermoplastic's mechanical behavior, the role of its average molar mass M¯n is rarely addressed, and many MD studies only consider uniform (monodispersed) polymers. Therefore, this contribution investigates the impact that M¯n and the dispersity Đ have on the stiffness and strength of PNCs through coarse-grained MD. To this end, we employed a Kremer–Grest bead–spring model and observed the expected increase in the mechanical performance of the neat polymer for larger M¯n. Our results indicated that the unimodal molar mass distribution does not impact the mechanical behavior in the investigated dispersity range 1.0≤Đ≤1.09. For the PNC, we obtained the same M¯n-dependence and Đ-independence of the mechanical properties over a wide range of filler sizes and contents. This contribution proves that even simple MD models can reproduce the experimentally well researched effect of the molar mass. Hence, this work is an important step in understanding the complex structure–property relations of PNCs, which is essential to unlock their full potential.
CRIS-Team Scopus Importer:2024-07-12
Keywords: Coarse graining; Glassy polymer; Mechanical properties; Molar mass distribution; Molecular dynamics; Polymer nanocomposites